Anion Influence on Supramolecular Interactions in Exo-Coordinated Silver(I) Complexes with N2O2 Schiff Base Macrocycle - Franc Perdih; Milenko Korica; Lorena Šebalj; Tomislav Balić (Crystals, 2022)
Silver(I) complexes with aza-oxa macrocyclic Schiff bases L (L = 1,5-diaza-2,4:7,8:16,17-tribenzo-9,15-dioxa-cyclooctadeca-1,5-dien) were prepared by the reaction of the corresponding macrocycle with four different silver salts (AgX; X = ClO4, PF6, SbF6 and BF4). In all four compounds, silver ions are exo-coordinated by two neighboring ligand molecules in linear and T-shaped geometries. Such a coordination mode results in the formation of infinite 1D polymeric chains. Compounds AgLClO4 and AgLBF4 are isostructural, and polymeric chains display 1D zigzag topology. In AgLPF6 there are three symmetrically unique Ag ions in the asymmetric unit of the compound. Two silver ions are linearly coordinated with two neighboring ligand molecules and are part of a discrete polymer chain. The third silver ion is coordinated with two ligand molecules and a methanol molecule in a T-shaped geometry. Such coordination geometry results in the formation of two discrete infinite polymer chains in the crystal structure. In the AgLSbF6 compound, the chain topology is a linear zigzag chain, but in this compound, there is a difference in the orientation of the Ag-N bond. The Ag-N-Ag bonds are in the trans position relative to the plane calculated through the ligand molecule, while the Ag-N bonds are in the cis position in all other compounds. Due to the presence of a bulky SbF6 anion, the ligand molecule is planar compared to other compounds. Considering intermolecular interactions, there is a huge variety of different interactions, mostly depending on the type of anion. A general supramolecular motif in all compounds is best described as 2D sheets of ligand–metal polymers with anions and solvent molecules sandwiched between them. In addition, the obtained compounds were characterized by IR spectroscopy and thermal analysis. The TG analysis indicates a rather surprising and considerable thermal stability of the prepared compounds, with some compounds thermally stable over 300 °C.